2017
DOI: 10.5688/ajpe5927
|View full text |Cite
|
Sign up to set email alerts
|

Design and Validation of Patient-Centered Communication Tools (PaCT) to Measure Students’ Communication Skills

Abstract: Objective. To develop a comprehensive instrument specific to student pharmacist-patient communication skills, and to determine face, content, construct, concurrent, and predictive validity and reliability of the instrument. Methods. A multi-step approach was used to create and validate an instrument, including the use of external experts for face and content validity, students for construct validity, comparisons to other rubrics for concurrent validity, comparisons to other coursework for predictive validity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…In this regard, Wallman et al revealed that in pharmacy education, good training occurs with patient-focused communication activities (e.g., learning interviewing techniques, patient counseling, or public health promotion) [28]. Other literature describes the introduction of student pharmacist assessments on oral patient communication (e.g., structured exam, pre/post evaluations) [70][71][72][73][74].…”
Section: The Educational System and The Futurementioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Wallman et al revealed that in pharmacy education, good training occurs with patient-focused communication activities (e.g., learning interviewing techniques, patient counseling, or public health promotion) [28]. Other literature describes the introduction of student pharmacist assessments on oral patient communication (e.g., structured exam, pre/post evaluations) [70][71][72][73][74].…”
Section: The Educational System and The Futurementioning
confidence: 99%
“…The outcomings from the FHM application in the pharmacy field raised the need for the ideation of a new instrument, specific to student pharmacist-patient communication skills, able to both measure communication and to assess the pharmacist-patient relationship. This framework, called the Patient-centered Communication Tools (PaCT), includes 23 skills organized into five general "tools" to be taught to students at an academic level [43,74].…”
Section: The Educational System and The Futurementioning
confidence: 99%
“…Previous studies have demonstrated the challenge of developing a communication rubric with a high level of interrater reliability. [10][11] The Patient-Centered Communication Tools (PaCT) developed by Grice and colleagues demonstrated a statistically significant correlation in interrater scores on two out of five assessment tools but no significant correlation on overall scores. The authors concluded that the interrater scores were not strongly correlated.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6] There are also numerous rubrics that have been proposed to assess communication skills within various environments. [7][8][9][10][11] To our knowledge, no study has utilized a coordinated evaluator training with a standardized codebook in an effort to increase reliability of a communication evaluation tool. Previously published studies have described methods for testing and achieving interrater reliability, however these were limited to single evaluator types.…”
Section: A J P Ementioning
confidence: 99%
“…Some of the evidence comes from education aids developed for patient-centered care in hospitals such as leaflets, brochures, etc. [28][29][30]. These validated education materials have the advantage of standardizing information to be shared with the participants and relieving discontent due to contradictory information [31].…”
Section: Discussionmentioning
confidence: 99%